Adjunctive Probiotic Lactobacillus rhamnosus Probio-M9 Administration Enhances the Effect of Anti-PD-1 Antitumor Therapy via Restoring Antibiotic-Disrupted Gut Microbiota - Gao, Guangqi; Ma, Teng; Zhang, Tao; Jin, Hao; Li, Yalin; Kwok, Lai-Yu; Zhang, Heping; Sun, Zhihong (Frontiers in Immunology, 2021)
Emerging evidence supports that the efficacy of immune checkpoint blockade (ICB) therapy is associated with host’s gut microbiota, as prior antibiotic intake often leads to poor outcome and low responsiveness towards ICB treatment. Therefore, we hypothesized that the efficacy of ICB therapy like anti-PD1-treatment required an intact host gut microbiota, and it was established that probiotics could enhance the recovery of gut microbiota disruption by external stimuli. Thus, the present study aimed to evaluate the effect of the probiotics, Lactobacillus rhamnosus Probio-M9, on recovering antibiotic-disrupted gut microbiota and its impact on the outcome of ICB therapy in tumor-bearing mice. We first disrupt the mouse microbiota by antibiotics and then remediated the gut microbiota by probiotics or naturally. Tumor transplantation was then performed, followed by anti-PD1-based antitumor therapy. Changes in the fecal metagenomes and the tumor suppression effect were monitored during different stages of the experiment. Our results showed that Probio-M9 synergized with ICB therapy and significantly improved tumor inhibition compared with groups not receiving the probiotic treatment (P<0.05 at most time points). The synergistic effect was accompanied by effective restoration of antibiotic-disrupted fecal microbiome, characterized by a drastically reduced Shannon diversity value and shifted composition of dominating taxa. Moreover, probiotic administration significantly increased the relative abundance of beneficial bacteria (e.g., Bifidobacterium pseudolongum, Parabacteroides distasonis, and some Bacteroides species; 0.0001